An Area Calculation of the ARBS Support Intensity - Keith A. Heasley; Aanand Nandula; Ihsan B. Tulu (International Conference on Ground Control in Mining, 2018)
"The objective of this paper is to present the development of a software tool that will assist in an area calculation of the Analysis of Roof Bolting Systems (ARBS) support intensity while incorporating more detailed geology, stress, and intersection span input. In this area ARBS tool, a detailed CMRR distribution can be determined from the available geologic database at the mine. In addition, the overburden and multiple-seam stresses, as obtained from the boundary-element program LaModel, can be converted to a “pseudo-depth” which is then used as the depth input to the area ARBS calculation. Finally, the section-specific intersection spans can be determined from the mine design for input to the calculation. All this detailed area input information for ARBS is handled by the latest version of the Stability Mapping (StabMap) program, which now outputs an area ARBS suggested support density given the required input parameters. This final ARBS grid can be plotted, analyzed and overlaid on the mine map for optimum use in support design and for presentation to production personnel.INTRODUCTIONSince the inception of roof bolts in the 1940s, there has been a lack of a universally accepted roof bolting design method (Mark, 2002; Mark and Pappas, 2012). To address this situation, the National Institute of Occupational Safety and Hazard (NIOSH) developed roof support design guidelines, which were incorporated into a computer program called the Analysis of Roof Bolting Systems (ARBS). These guidelines were based on the effects of roof quality, stress, and mine geometry (Mark, Molinda and Dolinar, 2001). The roof rock quality in ARBS is represented by the Coal Mine Roof Rating (CMRR), the depth is used as a surrogate for the stress, and the intersection span serves to represent the mine geometry (Mark, Molinda and Dolinar, 2001). These three input parameters are used in the fundamental, empirically derived equation of ARBS to calculate a required support density factor, called ARBS, (Mark, Molinda and Dolinar, 2001):"